Repair of fractured abutment teeth under pre-existing crowns: An alternative approach - Kennedy Mascarenhas; Meena A Aras; Aquaviva S Fernandes (Wolters Kluwer Medknow Publications, 2013)
This article describes a technique for repair of abutment tooth which fractured during removal of a provisional restoration before bisque trial. The technique uses plastic templates to fabricate new composite core foundation for the existing crowns. This technique helps the dentist to rebuild the core in a single appointment.